Technical Assistance Evaluation Program : Findings of Evaluations and Updated Program. (Policy Papers; Policy Paper ;, 2008)
Key Messages -- The Iraq Subaccount is a good example of donor coordination as expressed in the Paris Declaration. -- Overall, the TAs funded from the Iraq TA Subaccount were successful, relevant, efficient and effective. -- Ensuring long-term sustainability requires maintaining an adequate the level of TA activity in the future. -- There were instances where more pro-active donor coordination was needed to build synergies to achieve development results. -- While the offsite modality was fairly effective and cost efficient and delivered value for money, the limits of this model will be stretched as IMF moves from policy and operational advice and training to greater emphasis on supporting the implementation of policies and procedures. -- The Fund's internal monitoring needs to be strengthened, particularly the TA Information Management System. Reforms in this area are on track, supported by Fund management, and improvements are expected by 1 May 2008. -- The Fund's TA evaluation framework needs to be strengthened by instituting a system of self assessments of all completed TAs and developing guidelines for the ex-post evaluation of TAs. Work in these areas is planned. -- The Fund delivered slightly more internally funded TA to Iraq than originally planned.